2009
DOI: 10.1007/s11547-009-0395-5
|View full text |Cite
|
Sign up to set email alerts
|

Terapie ablative percutanee imaging-guidate nel trattamento delle metastasi ossee sintomatiche: esperienza preliminare

Abstract: Percutaneous ablation therapies represent a safe and valuable alternative for treating localised pain from single bone metastasis, providing rapid (4-week) relief of symptoms and a significant reduction in morphine doses. This contributes to improving the quality of life of patients with metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Microwave ablation is the most recent development in the field of tumor ablation [1,4,5,8]. Electromagnetic microwaves agitate water molecules in the surrounding tissue, producing friction and heat, thus inducing cellular death through coagulation necrosis [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave ablation is the most recent development in the field of tumor ablation [1,4,5,8]. Electromagnetic microwaves agitate water molecules in the surrounding tissue, producing friction and heat, thus inducing cellular death through coagulation necrosis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave ablation has shown potential in the treatment of primary and secondary liver disease, lung malignancies, and renal tumors [1,4,8]. Early clinical use of microwave ablation in primary bone tumors and bone metastases has been promising [5,11]. During the last decade, we performed joint-preservation surgery for patients with juxtaarticular osteosarcoma by transepiphyseal osteotomy after navigation-assisted microwave ablation of the edge of the tumor and reconstruction with an intercalary biologic reconstruction, preserving the native joint and maintaining a nearly normal joint.…”
Section: Introductionmentioning
confidence: 99%
“…A large randomized, controlled, multicenter phase III trial has shown Focused Ultrasound (FUS) to be effective in the treatment of painful bone metastases [17], confirming results of earlier retrospective reports [18]. Small case series also support benefit from other percutaneous methods of image-guided ablation, including microwave ablation, laser ablation, and irreversible electroporation to treat skeletal metastases, although the data are more limited [19][20][21][22][23][24][25][26]. These studies demonstrate that multiple ablation therapies are effective at palliation of pain due to metastatic skeletal disease.…”
Section: Resultsmentioning
confidence: 60%
“…A few limited reports of treatment of patients with metastatic disease have been reported with promising results. 39,40 Materials and technique Percutaneous microwave ablation is usually performed with the patient under conscious sedation 40 although in certain situations when procedural pain is problematic, a general anaesthesia may be required. 38 After local anaesthesia, a thin microwave antenna is introduced into the lesion under CT guidance.…”
Section: Microwaves Ablation Indicationsmentioning
confidence: 99%